2022
DOI: 10.3389/fpls.2022.1001992
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Interaction between zinc and selenium bio-fortification and toxic metals (loid) accumulation in food crops

Abstract: Biofortification is the supply of micronutrients required for humans and livestock by various methods in the field, which include both farming and breeding methods and are referred to as short-term and long-term solutions, respectively. The presence of essential and non-essential elements in the atmosphere, soil, and water in large quantities can cause serious problems for living organisms. Knowledge about plant interactions with toxic metals such as cadmium (Cd), mercury (Hg), nickel (Ni), and lead (Pb), is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The results obtained via immunological tests suggest that the highest biological activity occurs in L. edodes water extracts not supplemented with Se or Zn (Sample 0) or those where mycelium was enriched with a Se concentration of 0.2 mM and Zn at a concentration of 0.8 mM (Sample Zn/Se). Both analyzed T cell populations are essential with regard to protective immunity against viral infections, including SARS-CoV-2 [ 53 , 54 ] In our previous study, we demonstrated that the direction of L. edodes polysaccharides biological activity depends on the type of cell stimulation [ 43 ]. The present study confirms these observations.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained via immunological tests suggest that the highest biological activity occurs in L. edodes water extracts not supplemented with Se or Zn (Sample 0) or those where mycelium was enriched with a Se concentration of 0.2 mM and Zn at a concentration of 0.8 mM (Sample Zn/Se). Both analyzed T cell populations are essential with regard to protective immunity against viral infections, including SARS-CoV-2 [ 53 , 54 ] In our previous study, we demonstrated that the direction of L. edodes polysaccharides biological activity depends on the type of cell stimulation [ 43 ]. The present study confirms these observations.…”
Section: Discussionmentioning
confidence: 99%
“…due to accumulation [105]. Despite being a necessary element, selenium (Se) is harmful in greater amounts and is thus regarded as a worldwide contaminant [106]. Dimethyl selenide (DMSe), for example, is created by plants from selenium (Se).…”
Section: Recent Biotechnological Approaches For Potential Phytoremedi...mentioning
confidence: 99%